In Vitro Anti-Biofilm Activity of The Extract Of Pilea Cadierei - Zaichang, Yang; Du, Runzi; Zhang, Jian; Li, Qiang (Asian Journal of Pharmaceutical Research and Development, 2013)
Anti-biofilm activity of the Pilea cadierei on clinical isolated of Escherichia coli U 07 was employed using a crystal violetstained microtiter plate method and microscopic biofilm formation assay. The results indicated that crystal violet-stained microtiter plate method is not suitable to screen for biofilm formation inhibitors from crude plant extracts. Microscopic biofilm formation assay clearly showed the extract of Pilea cadierei can inhibit the Escherichia coli U 07 biofilm formation at concentration of 4 mg/ml. The results suggest that the Pilea cadierei could be a useful source for the development of promising anti-biofilm agents.